The Impact of Mobile Technology on English Writing Teaching: The Relationship between Interactive Feedback and Autonomous Learning Abilities - Deng, Weifeng; Wang, Lin (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rapid development of information technology (IT), mobile technology has been widely applied in the field of education, particularly in language learning. English writing, as one of the core skills in language acquisition, faces numerous challenges within traditional teaching models, such as limited learner autonomy and the difficulty of meeting individualized needs. In recent years, mobile technology-assisted English writing teaching has become a new research focus, with interactive feedback mechanisms and the enhancement of autonomous learning abilities being identified as key factors influencing instructional effectiveness. This study aims to explore mobile network-based English writing teaching, specifically analyzing how locationaware features and interactive feedback can enhance students’ autonomous learning abilities. In particular, the study investigates the forms and challenges of mobile network-assisted English writing teaching, examining mobile network discovery technologies, similarity calculation, and evolutionary computation methods relevant to English writing teaching, and proposes strategies for enhancing autonomous learning through interactive feedback.